Pseudomonas aeruginosa partitioning protein ParB acts as a nucleoid-associated protein binding to multiple copies of a parS-related motif - Kawalek, Adam (Nucleic Acids Res, 2018)
ParA and ParB homologs are involved in accurate chromosome segregation in bacteria. ParBs participate in the separation of ori domains by binding to parS palindromes, mainly localized close to oriC. In Pseudomonas aeruginosa neither ParB deficiency nor modification of all 10 parSs is lethal. However, such mutants show not only defects in chromosome segregation but also growth retardation and motility dysfunctions. Moreover, a lack of parB alters expression of over 1000 genes, suggesting that ParB could interact with the chromosome outside its canonical parS targets. Here, we show that indeed ParB binds specifically to hundreds of sites in the genome. ChIP-seq analysis revealed 420 ParB-associated regions in wild-type strain and around 1000 in a ParB-overproducing strain and in various parS mutants. The vast majority of the ParB-enriched loci contained a heptanucleotide motif corresponding to one arm of the parS palindrome. All previously postulated parSs, except parS5, interacted with ParB in vivo. Whereas the ParB binding to the four parS sites closest to oriC, parS1-4, is involved in chromosome segregation, its genome-wide interactions with hundreds of parS half-sites could affect chromosome topology, compaction and gene expression, thus allowing P. aeruginosa ParB to be classified as a nucleoid-associated protein.